Security protocols XXIV : 24th International Workshop, Brno, Czech Republic, April 7-8, 2016, Revised selected papers /: 24th International Workshop, Brno, Czech Republic, April 7-8, 2016, Revised selected papers. (2017) - Unknown
No abstract available